Pengaruh Profitabilitas Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening (Studi pada Perusahaan Sub Sektor Otomotif dan Komponen yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Surianingrat, Entol Muamar; Ichwanudin, Wawan (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2019)
This research examines and discovers the influence of profitability on firm value and capital structure as mediating effect at automotive and component companies which are listed on Indonesian Stock Exchange in 2013-2015 with 12 companies as total samples. This study using path analysis to solve the problem with the help of SPSS 24. The result shows that profitability and capital structure have positive effect on firm value, profitability has negative effect on capital structure, and then capital structure has no mediating effect between profitability and firm value